(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
Since the ’60s geologists discussed if the Tuscan Nappe includes the Macigno, the Mt. Modino Sandstone and the olistostromes interposed between these two clastic wedges or instead the foredeep deposits of the Tuscan Nappe is the Macigno and, therefore, the Mt. Modino Sandstone sedimented in a distinct basin and belongs to a different tectonic unit. One of the main difficulties to unravel the Macigno-Mt. Modino Sandstone relationships is the absence of continuous biostratigraphic records, helpful to date these formations and the underlying units. To fill this gap, a quantitative biostratigraphical analysis of calcareous nannofossils was performed on a large number of smear slides. The results confirm the stratigraphic continuity between the Tuscan Shale and the Macigno, and prove the stratigraphic continuity between the Fiumalbo Shale, the Marmoreto Marl and the Mt. Modino Sandstone (Mt. Modino Unit auctt.), supporting the tectonic superposition of the Mt. Modino Unit onto the Tuscan Nappe. In fact, the upper portion of the Tuscan Nappe ranges from the Late Eocene (MNP19/20) to the lower Miocene (MNN1c) and the Tuscan Shale-Macigno boundary lies within the upper Rupelian-Chattian (MNP24-MNP25a), whilst the sampled part of the Mt. Modino Unit spans in age the middle Eocene-lower Miocene (MNP15-MNN1c), and the Fiumalbo Shale-Marmoreto Marl and Marmoreto Marl-Mt. Modino Sandstone boundaries lie within the Rupelian (MNP23) and the uppermost Chattian (MNP25b-MNN1a).